PHOSPHATES ADSORPTION FROM WATER BY RECYCLED CONCRETE - Buriánek, Pavel; Skalický, Michal; Grünwald, Alexander (GeoScience Engineering, 2014)
It was only very recently that recycled concrete has also started to be used in water management primarily as a sorbent or reagent. Important factors influencing its use include mainly its origin, chemical, physical and mechanical characteristics. Adsorption kinetics was measured experimentally (Freundlich and Langmuir isotherm); and efficiency, values of adsorption capacity and changes of water chemical reactions due to added recycled concrete were found. Phosphates were removed either from standard solutions or from surface water.